ASPEK YURIDIS PERJANJIAN BUSINESS FRANCHISE DI INDONESIA - Lily Triana (Law Department, University of Widya Gama Mahakam Samarinda, 2018)
In Indonesia there is no regulation about franchise. Same thing is also experienced of many state, for example English and Australian. No special regulation about franchising can be consedered to be good news or is bad news. The bad news is wth no special guidance, hence goodnesss of franchisor amd also of franchisee have to reckon on written agreement in cooperation contract. Irts meaning both parties have to neglectless and meticulous to the what agreed on. Protection of other decision which arrange an cooperation of Franchising represent the source of which whereas can be made by guidance do complied agreement have the basis for real correct and fair. Association of franhcising generally realese code of ethic of franchising.good news of inexistence regulation of area of franchising is goodness of franchisor and fracnhisee earn free compromise whateverly. As hold of legal fundament of agreement of franchise in Indonesia is freedom contract such as those which arranged in section 1338 KUH Perdata and by concidering conditions of section 1338 KUHP Perdata. Law contract in Indonesia embrace open system meaning that each and everyone is free to make all kinds of contract. In section 1338 KUH Perdata contained by the following rule all made contract lawfully will bind over them making it own. In the case conditions of 1320 section of KUH this Perdata is fulfilled by hence comand of section 1338 KUH Perdata. The making agreement act as code/law to all party. So franchise, and vitally hence to all party arrange agreement content detail.Solving of dispute represent problem which in many is important to licencer, specially In the case of giving of license. Right of intellectual properties in the form of trade secret. Solving of dispute which is through jurisdiction forum, it is though enabled to be emphasized in conference closed (for the secret of trade) felt concerned abaout by licencer party will become an openly forum to receiver of license which do not good mine. To avoid the mentioned hence better each ; every dispute realted to agreement of giving license finished in framework of alternative of is solving of dispute, including in it arbitrase.Ordinary license agreement unlike giving of agreement of license of franchise. If at giving of agreement of license usually only covering giving of permission cover all sort of kinds of intellectual property that appliances bought or rented from him. Besides so-called above, agreement of franchise are; giving of license abaout name of trading, model brand, desain, ets. Rules that can be grouped in the field of contractual law and in the field of law about intellectual property.